Dinamika Politik Penguatan Kebijakan Sawit di Riau Pasca Reformasi - Khairul Anwar (Dinamika Lingkungan Indonesia, 2022)
This article aims to find the dynamics of actor interaction in strengthening oil palm policies with examples of cases of oil palm policy in Riau. The background is the phenomenon of the broader spectrum of conflict in Riau early in the reformation. How will the interaction pattern of actors related to oil palm policy issues take place in post-reform Riau? The theory used by the local political economy and the method used determine; (1) Actor's political preferences; (2) Actor's tips and strategies; and (3) How do actors organize themselves into coalitions? This study found that since the OTDA policy was implemented in Riau, the dynamics of national politics changed, from a central style to a decentralized one. This change in political context resulted in mixed responses from local actors in Riau. Local actors are becoming more critical because of the law on the use of natural resources. The activities of these different actors produce different reactions to implementing policies in the plantation sector. The response of these elites could be a result of different positions. Since the reformation, the intensity and spectrum of political dynamics have increased and expanded and its disclosure in public debate has become more assertive. It is a fact that the nature of local politics is considered in strengthening the policy on palm oil management in Riau.